The Development of Modernization Indicators in Pastoral Areas: A Case Study in Inner Mongolia - Yamei WANG; Haoji WANG; Xianjun SONG; Bohang YUAN; Yunshu WANG; Liwen WU; Min WANG; Boyi ZHAO (Chinese Journal of Urban and Environmental Studies)
This study employs a multi-indicator comprehensive entropy weight method to construct an indicator system comprising production systems, management systems, output efficiency, and social development indicators. It estimates the level of pastoral modernization in 33 pastoral banners and 21 semi-pastoral banners in the Inner Mongolia Autonomous Region from 2000 to 2021. The results indicate that the level of pastoral modernization in Inner Mongolia can be classified into three phases based on growth rates: growth phase, decline phase, and relative stability, with an overall upward trend. The ranking of first-level indicator scores is as follows: social development, management systems, output efficiency, and production systems. Utilizing the Exploratory Spatial Data Analysis (ESDA) method, the study analyzes regional disparities and employs an obstacle analysis to diagnose the main barriers to pastoral modernization development. The findings show that the level of modernization in semi-pastoral banners is generally higher than that in pure pastoral banners. Additionally, the level of pastoral modernization in the eastern region of Inner Mongolia is higher than in the western region. Key obstacles to pastoral modernization include the low proportion of pastoral value added to agricultural value added, total grain output, total industrial output above designated size, and total social electricity consumption. Although the level of pastoral modernization in Inner Mongolia is gradually improving, different regions and stages face distinct primary obstacles.